Efektifitas Intervensi Multidomain terhadap Resiko Penyakit Kardiovaskular pada Pra-Lansia di Jawa Barat - Herdiman; Nyayu Nina Putri Calisane; Linlin Lindayani (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Cardiovascular disease is the highest cause of death in Indonesia, which is also known as the “silent killer. However, research focused on preventing cardiovascular disease in the elderly is still very limited. In Indonesia, there is no multi-domain intervention using the internet that is intended to improve pre-elderly health.The aim of this study was to design an internet-based multidomain intervention program to prevent cardiovascular disease in the pre-elderly. This study used a quasi-experimental pre-post-test design with two groups (intervention group and control group). The inclusion criteria in this study were: elderly aged 55-65 years, had at least two risk factors for cardiovascular disease (such as hypertension, hypercholesterolemia, obesity, smoking, inactivity, DM, history of cardiovascular disease) previously to participate in the study. The sampling technique that will be used is the convivence sample with a total sample to be recruited is 100.The results of this study will be very useful as a guide for pre-elderly and health workers in the prevention of cardiovascular disease. It is hoped that the results of this study can be used as material for health policy makers in Indonesia to make guidelines and recommendations for disease prevention management in the pre-elderly.